Kerukunan sosial internal dalam jemaat: Refleksi teologis 1 Korintus 1:10-13 - Sumiwi, Asih Rachmani Endang; Sembodo, Joko; Santo, Joseph Christ (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
Harmony in society is an important thing that needs to be realized as an effort to suppress conflict with the nuances of SARA (ethnicity, religion, race, inter-group). The church needs to have sensitivity in contributing to realizing this harmony. Starting from the internal harmony of Christians, this harmony extends to social harmony. This article seeks to answer how Christians realize social harmony with regard to Paul's message on 1 Corinthians 1:10-13. This research was conducted with a qualitative literature approach, using an interpretive descriptive method on the text of 1 Corinthians 1: 10-13. The conclusion of this paper is that Christians need to participate in building social harmony starting from the internal harmony of the congregation, which is done in three ways: speaking the same things, which means having agreement; being closely united, which means being bound together; and having one mind, which means having similarities in thinking and considering. AbstrakKerukunan dalam bermasyarakat merupakan hal penting yang perlu diwujudkan sebagai upaya untuk menekan konflik dengan nuansa SARA. Gereja perlu memiliki sensitivitas dalam turut mewujudkan kerukunan tersebut. Diawali dari kerukunan intern umat Kristen, kerukunan ini meluas kepada kerukunan sosial. Artikel ini berusaha menjawab bagaimana orang Kristen mewujudkan kerukunan sosial berkenaan dengan pesan Paulus melalui 1 Korintus 1:10-13. Penelitian ini dilakukan dengan pendekatan kualitatif literatur, menggunakan metode deskriptif interpretatif atas teks 1 Korintus 1:10-13. Kesimpulan dari tulisan ini adalah, orang Kristen perlu turut membangun kerukunan sosial, yang dimulai dari kerukunan internal jemaat, dengan menerapkan tiga hal, yaitu: seia sekata, yang berarti memiliki kesepakatan; erat bersatu, yang berarti terikat bersama; dan sehati sepikir, yang berarti memiliki kesamaan dalam berpikir dan mempertimbangkan.